Application of mNGS in the study of pulmonary microbiome in pneumoconiosis complicated with pulmonary infection patients and exploration of potential biomarkers - Yuan, Xingya; Xie, Linshen; Shi, Zhenzhen; Zhou, Min (Frontiers in Cellular and Infection Microbiology, 2023)
Background Pneumoconiosis patients have a high prevalence of pulmonary infections, which can complicate diagnosis and treatment. And there is no comprehensive study of the microbiome of patients with pneumoconiosis. The application of metagenomic next-generation sequencing (mNGS) fills the gap to some extent by analyzing the lung microbiota of pneumoconiosis population while achieving accurate diagnosis. Methods We retrospectively analyzed 44 patients with suspected pneumoconiosis complicated with pulmonary infection between Jan 2020 and Nov 2022. Bronchoalveolar lavage fluid (BALF) specimens from 44 patients were collected and tested using the mNGS technology. Results Among the lung microbiome of pneumoconiosis patients with complicated pulmonary infection (P group), the most frequently detected bacteria and fungi at the genus level were Streptococcus and Aspergillus, at the species level were Streptococcus pneumoniae and Aspergillus flavus, respectively, and the most frequently detected DNA virus was Human gammaherpesvirus 4. There was no significant difference in α diversity between the P group and the non-pneumoconiosis patients complicated with pulmonary infection group (Non-P group) in pulmonary flora, while P< 0.01 for β diversity analysis, and the differential species between the two groups were Mycobacterium colombiense and Fusobacterium nucleatum. In addition, we monitored a high distribution of Malassezia and Pneumocystis in the P group, while herpes virus was detected in the majority of samples. Conclusions Overall, we not only revealed a comprehensive lung microbiome profile of pneumoconiosis patients, but also compared the differences between their microbiome and that of non-pneumoconiosis complicated with pulmonary infection patients. This provides a good basis for a better understanding of the relationship between pneumoconiosis and microorganisms, and for the search of potential biomarkers.